Strengthening Social Studies for Pancasila 5.0, Backgrounded by 'Society 5.0' - Christine Pheeney (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
Strengthening Social Studies for Pancasila 5.0, Backgrounded by 'Society 5.0' Presented by Christine Pheeney from Charles Darwin University